2007
DOI: 10.4067/s0716-97602007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of morphine-induced central respiratory depression by donepezil in the anesthetized rabbit

Abstract: Morphine is often used in cancer pain and postoperative analgesic management but induces respiratory depression. Therefore, there is an ongoing search for drug candidates that can antagonize morphine-induced respiratory depression but have no effect on morphine-induced analgesia. Acetylcholine is an excitatory neurotransmitter in central respiratory control and physostigmine antagonizes morphine-induced respiratory depression. However, physostigmine has not been applied in clinical practice because it has a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In conclusion, our results are consistent with previous reports showing interaction between opioidergic and cholinergic mechanisms in respiration in experimental animals (Berkenbosch et al, 1994;Bourke et al, 1984;Sakuraba et al, 2009;Tsujita et al, 2007;Weinstock et al, 1981) and in human subjects (Snir-Mor et al, 1983). Naloxone not only counteracts morphine-induced side effects but also inhibits morphine-induced analgesia (Bowdle, 1998).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In conclusion, our results are consistent with previous reports showing interaction between opioidergic and cholinergic mechanisms in respiration in experimental animals (Berkenbosch et al, 1994;Bourke et al, 1984;Sakuraba et al, 2009;Tsujita et al, 2007;Weinstock et al, 1981) and in human subjects (Snir-Mor et al, 1983). Naloxone not only counteracts morphine-induced side effects but also inhibits morphine-induced analgesia (Bowdle, 1998).…”
Section: Discussionsupporting
confidence: 95%
“…Moreover, the central chemosensitive area is proposed to be one of the sites of opioid action, because morphine decreases the sensitivity of hypercapnic response and because an antagonist of opioid receptors, naloxone, augments the respiratory neuronal response to CO 2 (Shook et al, 1990;Yeadom and Kitchen, 1989). It is reported that the opioid-induced respiratory depression is recovered by anticholinesterases, physostigmine (Berkenbosch et al, 1994;Bourke et al, 1984;Weinstock et al, 1980Weinstock et al, , 1981 and donepezil (Sakuraba et al, 2009;Tsujita et al, 2007). These findings raise a possibility that opioids negatively interact with the CO 2 -sensitive cholinergic transmission, presumably by depression of acetylcholine (ACh) release (Trouth et al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…The experimental procedure has been described in detail elsewhere (Kuwana and Natsui, 1981;Okada et al 2004;Tsujita et al 2007). Briefly, 15 healthy rabbits (Japanese White, male, Sankyo laboratory, Tokyo, Japan) 2.35 ± 0.08 kg (1.98-2.97 kg) were anesthetized by intraperitoneal administration of 10 mg/kg ketamine (Sankyo Pharmaceutical, Tokyo, Japan) followed by intravenous administration of 40 mg/kg chloralose and 200 mg/kg urethane (Wako Pure Chemical, Osaka, Japan).…”
Section: Generalmentioning
confidence: 99%
“…In our previous study, it was shown that donepezil, a long-acting synthetic drug widely used for Alzheimer's disease (Rho and Lipson, 1997), can reverse morphineinduced respiratory depression (Tsujita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It appears to improve sedation and fatigue in patients receiving opioids for cancer pain and prevents the addictive effect of morphine. Also it might enhance the analgesic effect of morphine because spinal Ach enhances the analgesic effect of systemic morphine [6].…”
mentioning
confidence: 99%